The psychology of religion and spirituality for clinicians : using research in your practice - Aten, Jamie D.; O'Grady, Kari Ann, 1969-; Worthington, Everett L., 1946- (New York : Routledge, 2012)
'The purpose of this edited book is to provide mental health practitioners with a functional understanding of the empirical literature on the psychology of religion and spirituality, while at the same time outlining clinical implications, assessments, and strategies for counseling and psychotherapy. This text is different from others on this topic because it will help to bridge the gap between the psychology of religion and spirituality research and clinical practice. Each chapter covers clinically relevant topics, such as religious and spiritual development, religious and spiritual coping, and mystical and spiritual experiences as well as discuss clinical implications, clinical assessment, and treatment strategies. Diverse religious and spiritual (e.g., Jewish, Islamic, Christian, and Buddhist, etc.) clinical examples are also be integrated throughout the chapters to further connect the psychology of religion and spirituality research with related clinical implications.'--
'The purpose of this edited book is to provide mental health practitioners with a functional understanding of the empirical literature on the psychology of religion and spirituality, while at the same time outlining clinical implications, assessments, and strategies for counseling and psychotherapy'--
Includes bibliographical references and index.
Keywords: Spirituality -- Psychological aspects; Psychology and religion; Psychology -- Religious aspects